Architectural Typology of the Old Russian Pillarless Churches of the pre-Mongolian Period - Trushnikova, Alexandra V. (Actual Problems of Theory and History of Art, 2015)
Pillarless churches were not typical for the Old Russian architecture of the pre-Mongolian period. The Church of Elijah the Prophet in Chernigov is the only one with surviving ancient vaults that represents Byzantine atrophied Greek cross type. The structure of other pillarless churches has traditionally been classified as pre-Mongolian version of the 15–16 centuries. “Pskov stair-step” type vaults that carried a dome narrower than a naos. However, such a design was still unknown in the 11–12 centuries. This article is an attempt to include Russian pre-Mongolian pillarless churches into Byzantine architectural typology. It invites us to look afresh at the churches and their possible reconstructions, taking into consideration all the peculiarities of their layouts and the results of most recent studies. At closer look number of churches turned out to be too large to have either «Pskov vaults» or any kind of vaulted structure without pillars. Two churches in Pereiaslavl’ and Vladimir-Volynskii (with parts of east wall protruding into the apse) are more likely to have had two-pillar structures. The article suggests that the church in Novii Olgov gorodok is a compact octagon in combination with cruciform layout. Along with St. Andrew church in Pereiaslavl’ (and perhaps “Staraia kafedra” in Vladimir-Volynskii) where galleries were added to the octagon type, these three examples represent Old Russian interpretation of the Byzantine architectural type. Old Russian single-nave churches on the whole were seldom as tiny as those in Byzantiium. This leads us to the assumption that their pilarless structure was determined not only by the scale of the building, but rather by the choice of specific type (e.g. compact octagon).